Pengaruh Pola Makan dan Aktivitas Fisik Terhadap Peningkatan Kadar Glukosa Darah Klien Diabetes Mellitus Tipe 2 : Literature Review - Ester Ronauli Sihotang (2020)
Diabetes mellitus is a chronic disease whose prevalence is very high where currently DM sufferers around the world are around 425 million people. In Indonesia, DM is the seventh leading cause of death with the incidence of DM in Jakarta as much as 3,4%. DM risk factors themselves one of them is a factor in physical activity and eating patterns that are not good. This study aims to summarize the results of previous studies regarding the relationship of diet and physical activity with increased blood glucose levels.Used the literature study method analyzed by topic.Based on 30 journals reviewed, diets such as low calorie diets, low carbohydrate diets, and high fat showed a decrease in blood glucose and HbA1c levels. In addition, consuming a high-fiber diet, the Mediterranean diet has increased blood glucose and HbA1c levels. The analysis of this research relates to Wahyuni and Moazezi's theories. High physical activity can reduce blood glucose levels compared to low activity. The analysis of this study is related to WHO theory and the American College of Sports Medicine (ACSM).The majority of journals get research results that have a relationship between diet and physical activity with an increase in blood glucose levels.